Medications affecting healing: an evidence‐based analysis. Issue 6 (25th September 2017) - Khalil, Hanan; Cullen, Marianne; Chambers, Helen; McGrail, Matthew
Abstract: The purpose of this arm of the study was to investigate the impact of medication on healing times of the various wound types, including acute wounds and leg ulcers. A prospective longitudinal study design was used, with de‐identified data collected using an electronic mobile wound care database system. Three main categories of data were collected, including patients' demographics, wounds types and treatment characteristics. For acute wounds, there was a total of 1732 patients with 2089 acute wounds. The average healing time was about 35 days. The only significant association was with chemotherapy, which increased healing time by 21 days ( P = 0·048). There were non‐significant trends towards reduced healing times with antibiotics (0·5 days; P = 0·853), anticoagulants (1·7 days, P = 0·673) and corticosteroids (4·98 days, P = 0·303). Non‐steroidal anti‐inflammatory drugs (NSAIDs) were associated with a non‐significant increase in healing time (2·17 days, P = 0·707). For leg ulcers, there was a total of 264 patients with 370 leg ulcers. We only examined the impact of antibiotics, anticoagulants, corticosteroids and NSAIDs on healing times as they had an adequate number of wounds to analyse. The average healing times of leg ulcers were found to be 73 days. None of the classes of medications had any significant impact on healing time. Both anticoagulants and NSAIDs increased healing time by (22·5 days, P = 0·08) and (12·5 days, P = 0·03), respectively. On the other hand, antibiotics and corticosteroids decreased healing times non‐significantly by (9·1 days, P = 0·33) and (21·6 days, P = 0·84), respectively.